Effect of integrated nutrient management on content and uptake of N, P, K and S of onion (Indian Journal of Arid Horticulture, 2025)
Onion is being cultivated in an area of about 0.42 million ha with a production of 4.21 million tonnes (Anonymous, 2004). The productivity of onion in India is, however, quite low compared to many other countries. Application of fertilizers is imperative to maintain the desired pace of crop production. Continuous use of inorganic fertilizers has depleted soil organic matter, resulting into inherent loss of native soil N, available P, available K and ultimately lowered the productions. Balanced fertilization has to be made for different crops based on soil testing for attaining maximum yield and nutrient content of crop. The balanced use of chemical fertilizers with FYM and biofertilizers for onion crop improve the nutrient availability and uptake to the plants.
Keywords: Onion; nutrient